GE_GERICHTE P/20091/2016 vom 16. Mai 2017 - GE Cour de justice (2017)
LÉSÉ ; VICTIME ; PERSONNE PROCHE ; PARTIE CIVILE ; QUALITÉ POUR RECOURIR ; TORT MORAL | CP.115; CP.127; CP.128; .19; .86; CPP.105; CPP.115; CPP.116; CPP.117; CPP.118; CPP.122; CPP.301; CPP.382; CO.47; CO.49